Industrial Training Report: Perpustakaan Tuanku Syed Faizuddin Putra Universiti Malaysia Perlis / Farah Amalina Adanan - Adanan, Farah Amalina (Faculty of Information Management, 2018)
Industrial training is an important phase of a student life. This purpose of this article is to show the value of library management internships in Perpustakaan Tuanku Syed Faizuddin Putra, Universiti Malaysia Perlis. Internships create real world learning opportunities for students in the course of Bachelor of Information Science in Library Management who have taken the introduction to library course. Students gain valuable hands-on experience processing some or all of a library collection under the supervision and mentoring of the Head Division within the library. The library benefits by addressing its backlog of unprocessed materials. In a time of staffing shortages, it is essential to devise innovative practices that solve the problem of managing work flow without compromising standards. The elements of ongoing and educate a successful librarian internship are also applicable in Perpustakaan Tuanku Syed Faizuddin Putra, Universiti Malaysia Perlis